(untitled) (Konferensiyalar | Conferences, 2023)
Games are fun activities that promote interaction, thinking, learning, and problem solving strategies. Often, games have an aspect that permits the players to produce information in a short time period. Some games require the players to engage in a physical activity and/or complete a mental challenge. ’Games… help the teacher to create contexts in which the language is useful and meaningful. The learners want to take part and in order to do so must understand what others are saying or have written, and they must speak or write in order to express their own point of view or give information.’ ’Language learning is a hard task which can sometimes be frustrating. Constant effort is required to understand, produce and manipulate the target language. Well-chosen games are invaluable as they give students a break and at the same time allow students to practice language skills. Games encourage learners to interact, cooperate, to be creative and spontaneous in using the language in a meaningful way.